2016
DOI: 10.1007/s00280-016-3217-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of nab-paclitaxel plus carboplatin and concurrent thoracic radiotherapy in patients with locally advanced non-small cell lung cancer

Abstract: This regimen is feasible and well tolerated for the treatment of patients with unresectable locally advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…In the study by Kurtul N. et al 18 increased SPARC expression was associated with poor prognosis when patients were treated with nab-paclitaxel and concurrent radiotherapy. In the study by Kaira K. et al 19 a combination of carboplatin and nab-paclitaxel plus radiotherapy was administered as first line in unresectable stage III NSCLC with safety and efficacy in patients ≤65 years of age. Nab-paclitaxel can be used in NSCLC as first line treatment as an alternative to best supportive care in the group of the “elderly” ≥75 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kurtul N. et al 18 increased SPARC expression was associated with poor prognosis when patients were treated with nab-paclitaxel and concurrent radiotherapy. In the study by Kaira K. et al 19 a combination of carboplatin and nab-paclitaxel plus radiotherapy was administered as first line in unresectable stage III NSCLC with safety and efficacy in patients ≤65 years of age. Nab-paclitaxel can be used in NSCLC as first line treatment as an alternative to best supportive care in the group of the “elderly” ≥75 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The most well‐studied NP example is the clinical use of NP albumin (nab)‐bound paclitaxel (nab‐PTX) for a variety of solid tumor malignancies, such as NSCLC, breast cancer, and pancreatic cancer. A phase 1 trial in advanced NSCLC showed that the combination of radiotherapy, nab‐PTX, and carboplatin produced an objective response in 71% of patients with acceptable toxicity . A phase 2 trial using nab‐PTX in 42 patients with recurrent, refractory ovarian cancer reported a 23% response rate, a 36% stable disease rate, a median OS of 17.4 months, and no grade 4 or higher adverse events .…”
Section: Emerging Therapeutic Drug‐delivery Strategies For Lrrmentioning
confidence: 99%
“…A phase 1 trial in advanced NSCLC showed that the combination of radiotherapy, nab-PTX, and carboplatin produced an objective response in 71% of patients with acceptable toxicity. 125 A phase 2 trial using nab-PTX in 42 patients with recurrent, refractory ovarian cancer reported a 23% response rate, a 36% stable disease rate, a median OS of 17.4 months, and no grade 4 or higher adverse events. 126 Polymeric NPs are particularly of interest, because they can be designed to be responsive to various triggering stimuli, including microenvironmental changes in temperature, pH, or hypoxia as well as magnetic or ultrasound activation.…”
Section: Peritoneal Surface Malignanciesmentioning
confidence: 99%
“…Moreover, a preclinical study showed that combining nab-PTX with RT represents an improvement in chemoradiotherapy [12]. Kaira et al reported a phase I study of weekly nab-PTX with carboplatin and RT in patients with LA-NSCLC [13]. In that study, the recommended doses were nab-PTX of 80 mg/m 2 and carboplatin of area under the time-concentration curve (AUC) 2 mg/mL/min.…”
Section: Introductionmentioning
confidence: 99%